Estimación de la eficiencia de los sistemas de tratamiento de aguas residuales para el sector textil en el cantón Pelileo - Erika Vaneza, Chuqui Guamán (2019)
The present study deals with the estimation of the efficiency of the treatment systems of the textile sector in the Pelileo canton, for which it was necessary a water analysis during the period July-August 2018 at the entrance and exit of the treatment plants in where parameters such as BOD, COD, flow, nitrates, sulphates, phosphates, color, SST, STD, conductivity, PH, T, detergents and oils and fats were monitored. Due to the large number of jean washing and dyeing companies, three of them were selected according to their high, medium and low production levels. For the interpretation of the data, three scenarios have been considered: efficiency calculation, input and output analysis and parameter correlation. The results indicate that none of the three treatment plants has a high efficiency because in all three cases it is less than 60%, there are parameters at the output of the plant that exceed the permissible limits established by environmental regulations and the existence of a Correlation between parameters such as sulfates, phosphates and nitrates and between oils and fats, BOD, COD.The results established a general vision of the situation of the treatment plants which allowed proposing improvement proposals for the problems identified through laboratory analysis and field experience that are focused on the BOD / COD, Control of nitrates detergents and sulfates, retention times and maintenance of tanks